Leakage free electrolyte engraved flexible supercapacitors from Chitosan/GO@MnCO3 polymer hydrogel chelate film under BMIMBF4 ionic liquid assistance. (November 2021) - Selvam, Samayanan; Yim, Jin-Heong
Highlights: Novel route focused for electrolyte engraved Chitosan/GO@MnCO3 chelate hydrogel film synthesis. The hydrothermal processed hydrogel film applied for leakage free flexible supercapacitors. The fabricated supercapacitor exhibits 312.5 Fg -1 specific capacitance. It performed excellent long term cyclic capacity preservation of ∼90%. Abstract: This study investigates leakage free electrolyte engraved flexible supercapacitors fabricated using Chitosan/graphene oxide@MnCO3 polymer hydrogel chelate films. The composite hydrogel film prepared under BMIMBF4 ionic liquid medium via single step hydrothermal technique. The crystalline properties, chemical compositions, surface morphological observations are examined by carrying out X-ray diffraction, X-ray photoelectron spectroscopy, Scanning electron microscopy studies. The XPS summaries of the composite hydrogel reveal typical peaks of Mn 2p1/2 (653.2 eV), Mn 2p3/2 (641.7 eV), N1s (401.1 eV), and C1s (285.6 eV). The fabricated supercapacitor exhibits notable gravimetric capacitance of 312.5 Fg −1 with good energy density. It performs good capacity retention around 87% after 10, 000 charge-discharge cycles. The flexible hydrogel-based supercapacitor may initiate the suitability for smart electronic devices and wearable electronics as energy storage system. Graphical abstract: Image, graphical abstract